Desorption of plasmid DNA from anion exchangers: Salt concentration at elution is independent of plasmid size and load. Issue 8 (27th February 2023) - Beck, Jürgen; Biechele, Matthias; Repik, Christoph; Gruber, Petra; Furtmüller, Paul G.; Hahn, Rainer
Abstract : Detailed studies on the sorption behavior of plasmids on anion exchangers are rare compared to proteins. In this study, we systematically compare the elution behavior of plasmid DNA on three common anion exchange resins using linear gradient and isocratic elution experiments. Two plasmids of different lengths, 8 and 20 kbp, were studied and their elution characteristics were compared to a green fluorescent protein. Using established methods for determining retention characteristics of biomolecules in ion exchange chromatography lead to remarkable results. In contrast to the green fluorescent protein, plasmid DNA consistently elutes at one characteristic salt concentration in linear gradient elution. This salt concentration was the same independent of plasmid size but differed slightly for different resins. The behavior is consistent also at preparative loadings of plasmid DNA. Thus, only a single linear gradient elution experiment is sufficient to design elution in a process scale capture step. At isocratic elution conditions, plasmid DNA elutes only above this characteristic concentration. Even at slightly lower concentrations most plasmids remain tightly bound. We hypothesize, that the desorption is accompanied by a conformational change leading to a reduced number of available negative charges for binding. This explanation is supported by structural analysis before and after elution.